2020
DOI: 10.1016/j.envpol.2019.113634
|View full text |Cite
|
Sign up to set email alerts
|

A national-scale characterization of organochlorine pesticides (OCPs) in intertidal sediment of China: Occurrence, fate and influential factors

Abstract: Organochlorine pesticides (OCPs) have been restricted for application for about 30 years in China. Intertidal zone is a sink for anthropogenic pollutants, and to better understand the current pollution status of OCPs in China, 324 surface sediment samples collected from 14 typical intertidal zones of China were analyzed for 22 OCPs. The total concentrations of OCPs ranged from 0.051 to 4141.711 ng/g, with DDTs and HCHs being the dominant components. Seasonal variations were not significant for most intertidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 59 publications
2
5
1
Order By: Relevance
“…Whereas, the comparison of the mean PCBs concentration in sediments of Post-monsoon with other studies showed that the ∑PCBs concentration of this study was significantly lower than those reported from Makelele, Kalamu, and Nsanga, Congo (Kilunga et al 2017); River Ravi, Pakistan (Baqar et al 2017); Liaohe River, China (Lv et al 2020); CauBay River, Vietnam (Toan and Quy 2015); Sarno River, Italy (Montuori et al 2014); Soan River, Pakistan (Malik et al 2014); and River Chenab, Pakistan (Eqani et al 2012). However, the ∑PCBs concentration was slightly lower or somewhat comparable to those studies recorded from River Thames, England (Lu et al 2017); Yamuna River, India (Kumar et al 2013); Songhua River, China (Cui et al 2016) and Bahlui River, Romania (Neamtu et al 2009).…”
Section: Comparison With Previous Studies Worldwidecontrasting
confidence: 85%
“…Whereas, the comparison of the mean PCBs concentration in sediments of Post-monsoon with other studies showed that the ∑PCBs concentration of this study was significantly lower than those reported from Makelele, Kalamu, and Nsanga, Congo (Kilunga et al 2017); River Ravi, Pakistan (Baqar et al 2017); Liaohe River, China (Lv et al 2020); CauBay River, Vietnam (Toan and Quy 2015); Sarno River, Italy (Montuori et al 2014); Soan River, Pakistan (Malik et al 2014); and River Chenab, Pakistan (Eqani et al 2012). However, the ∑PCBs concentration was slightly lower or somewhat comparable to those studies recorded from River Thames, England (Lu et al 2017); Yamuna River, India (Kumar et al 2013); Songhua River, China (Cui et al 2016) and Bahlui River, Romania (Neamtu et al 2009).…”
Section: Comparison With Previous Studies Worldwidecontrasting
confidence: 85%
“…In the present study, we found a positive correlation between concentrations of OCPs and TOC (R 2 ¼ 0.77). A similar tendency was reported by (Huo et al, 2017) in Lake Chaohu sediments, China and (Lv et al, 2020) in 14 typical intertidal zones of China. The average of TOC in the studied sediments of the shrimp ponds (1.9 ± 1.8%) was in medium level, that is lower to those coastal waters around intensive shrimp ponds in Lampung province, Indonesia (ranged between 0.30 and 9.85%, average 3.09%) and much lower to those from the 5-year-old shrimp culture ponds in the Shanyutan wetland of Min River estuary, South-east China (22.4 ± 2.0%) (Gao et al, 2019); comparable to those Cua Hoi Estuary (average 1.72%) and Han River Estuary (average 1.78%) in coastal area of central Vietnam (Tham et al, 2019).…”
Section: Organic Carbon and Sediment Grain Sizesupporting
confidence: 82%
“…Three ranges of SQGQ were categorized based on potential adverse biological effects of sediment contamination. They are: no biological effects (SQGQ < 0.1), moderate biological effects (0.1 ≤ SQGQ < 1), and high biological effects (SQGQ ≥ 1) (Tian et al 2013;Wang et al 2019;Lv et al 2020).…”
Section: Sediment Quality Guideline Quotient (Sqgq)mentioning
confidence: 99%